Retrospective evaluation of patients who ingested drugs to commit suicide - Yavuz, Erdal; Turgut, Kasim (Annals of Medical Research, 2021)
Aim: To analyze patients presenting to our hospital after ingesting drugs for suicide purposes.Materials and Methods: Adult patients that attempted suicide by ingesting drugs or other substances were retrospectively reviewedover a two-year period. The population of the study was determined among the patients diagnosed with the ICD-10 codes of X.40-X49 in hospital records. The patients were divided into two groups as hospitalized and discharged, and evaluated in terms of age, gender, substances ingested, number of different types of drugs ingested, the statement of life threatening status in forensic reports, whether gastric lavage or activated charcoal was applied, history of previous suicide attempts, presence of psychiatric diagnoses, and leukocyte count. Then, we investigated any statistical differences between the two groups.Results: A total of 216 adult patients with a mean age of 27.65 ± 9.45 years were included in the study. The hospitalization rate was 49.1%. Taking two or more different types of drugs, a high leukocyte count, application of gastric lavage and active charcoal, and the presence of life-threatening status in forensic report were found to be higher in the hospitalized group(p 0.05). In addition, it was determined that for suicide purposes, psychiatric drugs were mostly taken by the patients with previous psychiatric diagnoses while those without these diagnoses mostly used analgesics to attempt suicide (p
Keywords: Emergency; intoxication; suicide